Assessment of satisfaction level of community-based health insurance and associated factors among households in Akaki Kality subcity, Addis Ababa, Ethiopia: a cross-sectional study in 2023 - Kedir Hussein Abegaz; Trhas Tadesse Berhe; Alachew Wondie Tamrat; Habtewold Mulat; Natinael Muluneh; Getachew Weldeyohanes Tedla (BMJ Public Health, 2025)
Background In developing countries such as Ethiopia, financial barriers to accessing medical treatments have placed at significant risk of social and economic hardship. To address these critical issues, this study aimed to determine the satisfaction level of community-based health insurance (CBHI) members in Akaki Kality Sub City, Addis Ababa, Ethiopia, in 2023.Method A community-based cross-sectional study was conducted from 22 May 2023 to 22 June 2023, with 630 participants. A multistage sampling method was used by selecting 50% of districts and 30% of ‘subdistricts’. Systematic random sampling (with K=5) was employed for participant selection. Data were entered into Epi-data V.3.1 and analysed using SPSS V.25. Descriptive statistics were calculated to determine the level of satisfaction. Bivariate logistic regression was applied to assess the association with p values <0.25. Those variables which showed significant association were included in multivariate analysis. To control confounders, multivariate analysis was conducted with a p<0.05.Result The study revealed that the overall satisfaction for the -CBHI scheme was 53.5% (95% CI 49%, 57%). Factors influencing satisfaction included average monthly income (adjusted OR (AOR) 0.62; 95% CI 0.43, 0.88), frequency of health facility visits (AOR 0.34; 95% CI 0.25, 0.90), availability of prescribed drugs (AOR 1.77, 95% CI 1.08, 2.93) and perceiving CBHI as having valid management regulations (AOR 1.74; 95% CI 1.12, 3.46).Conclusions The study demonstrated that the overall satisfaction level with the CBHI scheme was relatively low compared with other studies. Measures should include enhancing medication and laboratory test accessibility and reinforcing CBHI management and regulatory processes through increased manpower and improved monthly income level.